Insights for Preaching and Teaching Hebrews - Canoy, Robert (Review and expositor, 2005)
The purpose of this article is to provide a practical aid to preachers and teachers in their tasks of proclaiming Hebrews. After suggesting how proclaimers may prepare themselves to read the book, the article summarily explores the major theological themes found throughout Hebrews from the vantage point of how the themes potentially may be related through preaching and teaching. Included in the article is an exploration of some of Hebrews' challenging passages with suggestions of how to address them constructively. Proceeding from the presupposition that the document is sermonic, eschatological, and thoroughly theological, each of these is addressed throughout. The article urges that preaching and teaching done from Hebrews should be intentionally theo-logical and suggests that proclaimers should allow the text to guide the preaching and teaching that they do from it, following the interactive design pattern of exposition-exhortation. Five thematic sections are examined for homiletical insights. Although a verse-by-verse exposition is neither encouraged nor discouraged, preachers and teachers are reminded to make the very point(s) made by the writer of Hebrews and never to allow any personal agenda to take priority over authorial intention. To aid in the task of relevant preaching and teaching, sermon and lesson ideas, as well as supporting contemporary resources, are suggested.